ANALISIS SPASIAL DAN SEBARAN FASILITAS PENDIDIKAN TINGKAT SMP DAN SMA DI KABUPATEN KOLAKA - Rika Ristiani Asnia; Hasbullah Syaf; Djafar Mey (Universitas Halu Oleo, 2020)
The problem that is being faced in the development of education in Kolaka Regency is education infrastructure which is adequate in terms of quantity and quality. Based on BPS data in 2016, the population of Kolaka Regency amounts to 246,918 people, with the number of Senior High School level as many as 26 school units. This means that the ratio of each one school serves ± 9496 people, while according to Ministerial Regulation No. 24 of 2007, the ideal ratio for Senior High School level is that one school serves 6000 people. Therefore, this is one of the quantity problems in education in Kolaka Regency. In planning these facilities and infrastructures, then there are a number of things that need special attention, namely about the education facilities in Kolaka Regency. The purpose of this study was to identify the availability of the Educational Facilities at Junior and Senior High School Levels in Kolaka Regency and to analyze the needs and the distribution of the Educational Facilities at Junior and Senior High School Levels in Kolaka Regency. The study was conducted in qualitative and quantitative descriptive using the approach of the spatial analysis. Based on the results of this research conducted, the results of the assessment of the Educational Facilities at Junior and Senior High School Levels consist of the needs of the population and the capacity of schools in Kolaka regency, namely the needs of the age population at Junior and Senior High School Levels are good whereas the capacity of Junior High Schools is also good, but the capacity of Senior High Schools is in the less category. Analysis of education facilities at Junior High Schools in Kolaka Regency in 2027 is still needed to add 236 study groups to maximize the capacity of each school and does not need for additional schools. While at Senior High Schools as many as 188 study groups are needed and there is one sub-district that does not need the additional school in the next 10 years, namely the Tanggetada Sub-District. Keywords: Spatial Analysis, Distribution of Educational Facilities